Contact-induced deformation and damage of rocks used in pavement materials. (5th November 2017) - Celma Cervera, Carlos; Jelagin, Denis; Partl, Manfred N.; Larsson, Per-Lennart
Highlights: Experimental contact mechanics basis for DEM modelling of stone-based construction materials is presented. Dependency of stones contact law parameters on stress level, load history and surface roughness is demonstrated. Contact damage mechanisms controlling stones local wear and fragmentation are identified, demonstrated and quantified. Workflow to incorporate the reported experimental findings into DEM through particle contact and failure laws is proposed. Graphical abstract: Abstract: Performance of stone-based construction materials, such as asphalt and unbound aggregate mixtures is defined to a great extent by the mechanics of the stone-to-stone interactions. Accordingly, the Discrete Element Method (DEM) is gaining popularity as a modelling tool to investigate the mechanical behavior of these materials. Contact and failure laws defining particles force-displacement relationships and the propensity of particles to break are crucial inputs for the DEM simulations. The present study aims at providing an experimental contact mechanics basis for the development of physically based stone-to-stone interaction laws. The attention is focused on investigating stone's force-displacement relationship and damage characteristics at pure normal loading for two stone materials used by the road industry. Experiments are performed at spherical contact profiles for cyclic and monotonically increasing loads. The emphasis lies on the evolution of contact compliance and accumulation of contact induced damage. The effect of surface roughness on the materials response is examined through comparative experiments performed on the specimens with different roughness values. Optical and environmental scanning electron microscopy (ESEM) observations of the contact induced damage at the material surface are presented and discussed in the context of contact mechanics. The implications of the reported experimental findings on the development of mechanics based contact and failure laws for the DEM modelling of stone-based construction materials are discussed.